Capture and utilization of carbon dioxide from the lime kilns of a kraft pulp mill for bio-methanol production: Case study at the market pulp mill Södra Cell Mönsterås - Lindström, Vendela (My University, 2023)
Bio-methanol is a valuable product that can be used for a variety of applications. Södra Cell Mönsterås, a pulp mill situated in southern Sweden, currently produces bio-methanol as a byproduct from the pulping process. However, methanol could also be produced through carbon capture and utilisation (CCU), i.e. by capturing carbon dioxide from point emission sources at the plant site and reacting it with hydrogen. This master thesis aims to investigate the potential integration of such a CCU concept at Södra Cell Mönsterås, thus potentially increasing bio-methanol production on site. The carbon dioxide was assumed to be captured through post-combustion capture using an amine-based absorption process. For energy-efficient carbon dioxide capture, a high concentration of carbon dioxide in the flue gas is favorable. Consequently, the lime kilns of the mill were selected as potential carbon dioxide sources, since they have the highest concentration of carbon dioxide in the flue gases of the emission sources at the pulp mill. A 90 % capture rate of carbon dioxide from the flue gases of both kilns was assumed, corresponding to a total of approximately 230 kton/year of captured biogenic carbon dioxide, which could be used to produce 170 kton/year of bio-methanol, requiring 30 kton/year of hydrogen. For the energy balances, two levels of specific heating demands for the carbon capture process were evaluated. As a conservative estimate, a literature value for a standard capture process using a mono-ethanolamine (MEA) absorption solvent applied to typical combustion flue gases was considered, with a heating demand of 3600 kJ/kg carbon dioxide captured. To get an estimate of potential improvements with a more optimized process design and better performing solvents, a lower specific heating demand of 2900 kJ/kg carbon dioxide captured, which has been reported for the solvent blend amino-2-methyl-1-propanol/piperazine (AMP/PZ), was also evaluated. This resulted in a heating demands of 230 GWh/year and 186 GWh/year for the higher and lower value, respectively, when capturing 90 % of the carbon dioxide from the lime kilns. The results also indicate that the heating demand for the whole CCU concept can be covered by steam that could be made available from the mill, more specifically by bypassing the condensing turbine. However, the electricity demand for the electrolyser seems to be a more limiting factor. Production of 30 kton/year of hydrogen requires an elctrolyser with a total capacity of 260 MW of electric power input, corresponding to an electricity demand of 2.2 TWh/year. This can be compared to the current electricity consumption of the whole pulp mill, which was 0.7 TWh in 2021. One possibility could be to size the capture plant for maximum (90%) capture from both lime kilns, but only use part of the captured carbon dioxide for methanol production and sell the surplus or send it to permanent storage. Thus lowering the electricity demand for production of hydrogen at site.